A phytochemical investigation of the volatile oil of Wedelia biflora (Linn.) DC. (Family Compositae) - Chavez, Dario Gabriel M.
Wedelia biflora is a climbing, somewhat rough, herbaceous vine. The leaves are opposite ovate, and 6 to 8 cm long, with pointed top and rounded base, rather coarsely toothed margin, and stalks 2 to 6 cm long. The heads are 3 cm in diameter or less, and number 1 to 3, sometimes more in the upper axils, with stalks 7 to 10 cm long.